2011
DOI: 10.1007/s00449-011-0641-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of xylitol production in Candida tropicalis by co-expression of two genes involved in pentose phosphate pathway

Abstract: The yeast Candida tropicalis produces xylitol, a natural, low-calorie sweetener whose metabolism does not require insulin, by catalytic activity of NADPH-dependent xylose reductase. The oxidative pentose phosphate pathway (PPP) is a major basis for NADPH biosynthesis in C. tropicalis. In order to increase xylitol production rate, xylitol dehydrogenase gene (XYL2)disrupted C. tropicalis strain BSXDH-3 was engineered to co-express zwf and gnd genes which, respectively encodes glucose-6-phosphate dehydrogenase (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
7

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 22 publications
0
16
0
7
Order By: Relevance
“…The xylE activity assay (20) confirmed their much stronger activities than the control promoter, ermE* p , (Figure 1b), which is the mutated variant of the promoter of the erythromycin resistance gene from Saccharopolyspora erythraea , and is believed to be one of the strongest constitutive promoters in Streptomycetes (21, 22). The strong activities of gapdh p and the promoters of various translation elongation factors have also been observed in many other microorganisms, such as fungi, bacteria, micro-algae, and protozoa (2329). Encouraged by the strong activities of gapdh p and rpsL p , we decided to examine their equivalents from other species.…”
Section: Resultsmentioning
confidence: 83%
“…The xylE activity assay (20) confirmed their much stronger activities than the control promoter, ermE* p , (Figure 1b), which is the mutated variant of the promoter of the erythromycin resistance gene from Saccharopolyspora erythraea , and is believed to be one of the strongest constitutive promoters in Streptomycetes (21, 22). The strong activities of gapdh p and the promoters of various translation elongation factors have also been observed in many other microorganisms, such as fungi, bacteria, micro-algae, and protozoa (2329). Encouraged by the strong activities of gapdh p and rpsL p , we decided to examine their equivalents from other species.…”
Section: Resultsmentioning
confidence: 83%
“…In Candida utilis , for example, two enzymes involved in the pentose phosphate pathway (PPP) including glucose-6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase are responsible for the production of the required NADPH [17]. A study by Ahmad et al [5] showed that overexpression of these two enzymes led to an increase in xylitol production in Candida tropicalis .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been carried out for xylitol production in yeast, especially in Candida species and Saccharomyces cerevisiae [57]. However, fewer studies have been completed on xylitol production in T. reesei .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the control promoter, much stronger activities of gapdh p (SG) and rpsL p (SG) should be observed. The strong activities of gapdh p and the promoters of various translation elongation factors have also been observed in many other microorganisms, such as fungi, bacteria, micro-algae, and protozoa (Krasny et al, 2000;Suarez et al, 2006;Ahn et al, 2007;Shao et al, 2009;Hong et al, 2010;Ahmad et al, 2012;Jia et al, 2012). Cloning additional promoters 24.…”
Section: Now the Synthesized Cdna Is Ready For Real-time Pcrmentioning
confidence: 94%